Hydrothermal synthesis and characterization under dynamic conditions of cobalt oxide nanoparticles supported over magnesium oxide nano-plates. Issue 24 (16th March 2016) - Alayoglu, Selim; Rosenberg, Daniel J.; Ahmed, Musahid
Abstract : Surface evolution of a nano-catalyst comprised of oxidized Co NPs and MgO nano-plates was studied under O2, H2 and H2 + CO atmospheres using synchrotron-based X-ray spectroscopies. Abstract : A nano-catalyst comprised of oxidized Co NPs supported on MgO nano-plates was synthesized via a hydrothermal co-precipitation strategy and calcination in O2 and subsequently in H2 at 250 °C. Spectro-microscopy characterization was performed by scanning transmission electron microscopy, electron energy loss spectroscopy and scanning X-ray transmission microscopy. Surface measurements under H2 and H2 + CO atmospheres were obtained by ambient pressure X-ray photoelectron spectroscopy and in situ X-ray absorption spectroscopy in the 225–480 °C range. These measurements at the atomic and microscopic levels demonstrated that the oxidized Co nanoparticles uniformly decorated the MgO nano-plates. The surfaces are enriched with Co, and with a mixture of Co(OH)2 and CoO under H2 and H2 + CO atmospheres. Under a H2 atmosphere, the outermost surfaces were composed of (lattice) O 2−, CO3 2− and OH − . No inorganic carbonates were observed in the bulk. Chemisorbed CO, likely on the oxidized Co surfaces, was observed at the expense of O 2− under 300 mTorr H2 + CO (2 : 1) at 225 °C. Gas phase CO2 was detected under 32 Torr H2 + CO (2 : 1) at 225 °C upon prolonged reaction time, and was attributed to a surface chemical reaction between O 2− and chemisorbed CO. Furthermore, sp 3 like carbon species were detected on the otherwise carbon free surface in H2 + CO, which remained on the surface under the subsequent reaction conditions. The formation of sp 3 like hydrocarbons was ascribed to a surface catalytic reaction between the chemisorbed CO and OH − as the apparent hydrogen source.